Anxiety and the Equation : Understanding Boltzmann's Entropy - Johnson, Eric (Associate professor of chemistry) (Book collections on Project MUSE., 2018)
"This is a story about a man and his equation. We learn in this story that entropy is the central quantity in something called the second law of thermodynamics. The second law is always on, running in the background of our lives, providing us with a way to differentiate between past and future. It provides us with an arrow of time: we know that the future will be a state of higher entropy than the past. And we have Boltzmann to thank for discovering the equation that underlies that fundamental trend. The manuscript assembles the equation S = k log W (where S represents entropy) from its constituent parts. Throughout the book, the author also introduce scenes from Boltzmann's life and explores the nature of his mental illness, which he concludes was primarily an anxiety disorder. His goal is to build a meaningful equation and a sympathetic portrayal of a man whose flaws were as compelling as his intellect"--